Bridging Technology and Emotion: How Interaction Shapes Student Engagement in Blended Learning - Ahmad Shofi M; Rian Permana Suryadipraja; Rahman Tanjung (Information Technology Education Journal, 2025)
Interaction has become a central determinant of learning success in blended education, particularly in shaping students’ emotional, cognitive, and behavioral engagement. From the perspective of educational psychology, interaction fulfills basic psychological needs autonomy, competence, and relatedness yet its empirical role in secondary education contexts remains underexplored. This quantitative causal-comparative study involved 180 students from three secondary schools in Kendal Regency, Central Java, implementing blended learning. Data were collected using validated Likert-scale questionnaires based on the Online Student Engagement Scale (OSE) and the Blended Learning Interaction Scale (BLIS). Descriptive and inferential analyses were conducted using SPSS 26, including correlation and multiple regression tests.Findings show that all forms of interaction teacher–student (β = 0.382), student–student (β = 0.304), and student–content (β = 0.261) significantly affect student engagement (p < 0.001), explaining 61% of its variance (R² = 0.61). Teacher–student interaction emerged as the strongest predictor, emphasizing the continuing importance of pedagogical and emotional support in hybrid learning environments.Interaction quality, rather than technology alone, determines sustained engagement by fulfilling psychological needs and promoting intrinsic motivation. Practically, schools should strengthen teacher facilitation skills, peer collaboration mechanisms, and content interactivity in digital platforms. The study contributes to the integration of Self-Determination Theory and Community of Inquiry frameworks, offering insights for designing interaction-centered pedagogy that fosters emotional well-being and meaningful engagement in blended learning.